2002
DOI: 10.1103/physreva.66.042505
|View full text |Cite
|
Sign up to set email alerts
|

Emission spectra of Cs-He excimers in cold helium gas

Abstract: We observed broadband emission spectra of Cs-He excimers (Cs*He) in cold He gas (1.3-100 K), when Cs atoms were excited to the 6 2 P states. We calculated the emission spectrum from each vibrational state of Cs*He using Pascale's semiempirical Cs-He potential energy curves ͓J. Pascale, Phys. Rev. A 28, 632 ͑1983͔͒, and compared the results with the observed spectra. From the measured spectral shape, we estimated the relative populations of the vibrational states of Cs*He at various He gas densities, and estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
37
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 23 publications
10
37
1
Order By: Relevance
“…The formation of alkali-helium exciplexes was considered for the first time by Dupont-Roc [1] and Kanorsky et al [2] as an explanation for the observed quenching of atomic fluorescence from light alkali atoms (Na, Li) embedded in liquid and solid 4 He. In the meantime such exciplex molecules have been observed in liquid helium and in cold helium gas [3][4][5], as well as on the surface of helium nanodroplets [6][7][8][9]. In this paper we present a theoretical and experimental study of cesium-helium exciplexes formed in a solid helium matrix, and give a more detail account on our recent observation [10] of these complexes.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The formation of alkali-helium exciplexes was considered for the first time by Dupont-Roc [1] and Kanorsky et al [2] as an explanation for the observed quenching of atomic fluorescence from light alkali atoms (Na, Li) embedded in liquid and solid 4 He. In the meantime such exciplex molecules have been observed in liquid helium and in cold helium gas [3][4][5], as well as on the surface of helium nanodroplets [6][7][8][9]. In this paper we present a theoretical and experimental study of cesium-helium exciplexes formed in a solid helium matrix, and give a more detail account on our recent observation [10] of these complexes.…”
Section: Introductionmentioning
confidence: 99%
“…For cesium, however, the exciplex with three helium atoms is unstable and therefore its formation and hence the subsequent formation of larger exciplexes was expected to be suppressed. Experiments in cold helium gas, in which the relatively low collision rate justifies an analysis in terms of sequential capture processes, have indeed shown [3] that only Cs * He 1 and Cs * He 2 exciplexes are formed, with no evidence for complexes with n > 2.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These quasimolecular structures arising from the highly anisotropic alkali-metal-helium interaction have been analyzed in detail in [25,[38][39][40][41]. The dependence of the exciplex populations on He temperature and density in the range of ρ 0 = 10 18 -10 19 cm −3 was studied experimentally in [38,42]. Neglecting the population of the exciplex states, especially those in the B 3/2 electronic state, leads mainly to a discrepancy between the experimental and calculated spectra in the range of 930-980 nm (see Fig.…”
Section: Discussionmentioning
confidence: 99%